Influence of AlN reinforcement on properties of AA5083 matrix composite. (2023) - Jasmin, N.M.; Saravanakumar, M.; Nalini Suja, R.; Deshini, Aravind; Srikanth, S.; Ram, S.; Dinesh Kumar, S.
Highlights: The material properties of metal matrix are enhancing gradually by the accumulation of aluminium nitride (AlN). It has high temperature resistance. In current scenario, aluminium composite is playing a vital role in industrial applications. AlN reinforced AA5083 is synthesized by stir casting route. The material properties of AA5083 composite are evaluated with and without AlN. The great enhancement of substance properties such as tensile strength, hardness and impact strength are achieved by the presence of AlN. Taguchi approach is used to optimize the stir casting factors. Abstract: The material properties of metal matrix are progressively enhancing by the accumulation of aluminium nitride (AlN). It has high temperature resistance. In current scenario, aluminium composite is playing a vital role in industrial applications. AlN reinforced AA5083 is synthesized by stir casting route. The material properties of AA5083 composite are evaluated with and without AlN. The great enhancement of substance properties such as tensile strength, hardness and impact strength are achieved by the presence of AlN. Taguchi approach is used to optimize the stir casting factors. The aim of the research work is to increase the performance of AA5083 composite. Tensile strength has been increased from 355 MPa to 400 MPa by the addition of AlN particles.